Active Methanotrophs and Their Response to Temperature in Marine Environments: An Experimental Study - Jing Li (MDPI AG, 2021)
Aerobic methane (CH4) oxidation plays a significant role in marine CH4 consumption. Temperature changes resulting from, for example, global warming, have been suggested to be able to influence methanotrophic communities and their CH4 oxidation capacity. However, exact knowledge regarding temperature controls on marine aerobic methane oxidation is still missing. In this study, CH4 consumption and the methanotrophic community structure were investigated by incubating sediments from shallow (Bohai Bay) and deep marine environments (East China Sea) at 4, 15, and 28 °C for up to 250 days. The results show that the abundance of the methanotrophic population, dominated by the family Methylococcaceae (type I methanotrophs), was significantly elevated after all incubations and that aerobic methane oxidation for both areas had a strong temperature sensitivity. A positive correlation between the CH4 oxidation rate and temperature was witnessed in the Bohai Bay incubations, whereas for the East China Sea incubations, the optimum temperature was 15 °C. The systematic variations of pmoA OTUs between the Bohai Bay and East China Sea incubations indicated that the exact behaviors of CH4 oxidation rates with temperature are related to the different methanotrophic community structures in shallow and deep seas. These results are of great significance for quantitatively evaluating the biodegradability of CH4 in different marine environments.